PENERAPAN PERMAINAN SMALL SIDE GAMES TERHADAP HASIL BELAJAR PASSING DALAM PERMAINAN SEPAK BOLA - Dendi Irawan (STKIP Muhammadiyah Kuningan, 2021)
The purpose of this study was to determine the application of small sided games to the learning outcomes of passing in a football game. The research method used is an experimental method with a one-group pretest-posttest research design. The population in this study were students of SSB KU-12 Pegasus Ciwaru with a sampling technique using total sampling. The data analysis technique used by researchers was to test for normality, test for homogeneity and test hypotheses. The result of this research is the value of sig (2-tailed) 0.000. Because the value of sig ( 2-tailed ) 0.000 < 0.05 , thus H0 is rejected and H1 is accepted. This means that there is a treatment effect of the application of small sided games on the learning outcomes of passing in football games for students of KU-12 SSB Pegasus Ciwaru.